2015
DOI: 10.1002/anie.201504379
|View full text |Cite
|
Sign up to set email alerts
|

Methylamine‐Gas‐Induced Defect‐Healing Behavior of CH3NH3PbI3 Thin Films for Perovskite Solar Cells

Abstract: We report herein the discovery of methylamine (CH3NH2) induced defect-healing (MIDH) of CH3NH3PbI3 perovskite thin films based on their ultrafast (seconds), reversible chemical reaction with CH3NH2 gas at room temperature. The key to this healing behavior is the formation and spreading of an intermediate CH3NH3PbI3⋅xCH3NH2 liquid phase during this unusual perovskite-gas interaction. We demonstrate the versatility and scalability of the MIDH process, and show dramatic enhancement in the performance of perovskit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
469
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 398 publications
(491 citation statements)
references
References 22 publications
18
469
2
Order By: Relevance
“…[141] Therefore, overall film quality is improved by the reduction of grain boundaries, improvement of crystallinity and passivation of grain boundaries by excess PbI2.…”
Section: Additive Mediated Crystallizationmentioning
confidence: 99%
See 1 more Smart Citation
“…[141] Therefore, overall film quality is improved by the reduction of grain boundaries, improvement of crystallinity and passivation of grain boundaries by excess PbI2.…”
Section: Additive Mediated Crystallizationmentioning
confidence: 99%
“…(g-i) Reproduced with permission. [141] Copyright 2016, Wiley. [178] thin film ITO/PEDOT:PSS/MAPbBr3/ZnO/Ca/Ag 21 -550 2 -- [179] thin film ITO/Buf-HIL/MAPbBr3/TPBi/LiF/Al 0.577 0.125 417 4 543 20 [60] thin film ITO/c-TiO2/EA/MAPbBr3/SPB-02T/MoO3/Au 0.22 0.051 544 ~2.3 -- [27] thin film ITO/ZnO-PEI/MAPbBr3/TFB/MoO3/Au -0.8 20000 2.8 532 22 [180] thin film ITO/ZnO-PEI/MAPbI3-nCln/TFB/MoOx/Au -3.5 28* 2.2 768 37 [180] Polymer blending thin film ITO/MAPbBr3-PEO/In/Ga 0.38 0.083 4064 2.9 532 23 [181] thin film ITO/MAPbBr3-PEO/AgNWs 4.91 1.1 21014 2.6 -- [182] thin film ITO/PEDOT:PSS/MAPbBr3-PIP/F8/Ca/Ag -1.2 200 ~3.1 534 19 [183] Solvent treatment thin film ITO/PEDOT:PSS/MAPbBr3/SPB-02T/LiF/Ag 0.43 0.1 3490 ~2.1 540 - [184] thin film ITO/PEDOT:PSS/MAPbBr3/Bphene/LiF/Ag 0.54 0.13 3846 3.2 528 21 [185] thin film Glass/SOCP/MAPbBr3/TPBi/LiF/Al 42.9 8.53 15000 4 -- [14] Inorganic substitution thin film ITO/PEDOT:PSS/CsPbBr3/F8/Ca/Ag 0.035 0.008 407 3 527 18 [186] Nanostructuring nano plate ITO/PEDOT:PSS/MAPbBr3/PVK:PBD/BCP/LiF/Al -0.48 10590 3.8 20 [187] nano plate ITO/PEDOT:PSS/FAPbBr3:LiCF3SO3:TMPE/Al --1.3 11~1 2 -- [188] QD ITO/PEDOT:PSS/PVK/FAPbBr3/TPBI/LiF-Al 0.43 0.12 946 4.2 514 23 [189] QD ITO/PEDOT:PSS/PVK/CsPb(Cl/Br)3 /TPBI/LiF-Al 0.14 0.07 742 5.1 452 20 [189] QD ITO/PEDOT:PSS/PVK/CsPb(Br/I)3/TPBI/LiF-Al 0.08 0.09 528 4.6 586 23 [189] thin film ITO/PEDOT:PSS/CsPbBr3/B3PYMPM/CsCO3/Al 0.57 0.15 7276 2.8 524 18 [190] nano particle ITO/PEDOT:PSS/Poly-TPD:PFI/CsPbBr3/TPBi/LiF/Al 0.19 0.06 1377 3.5 516 18 [13] nano particle ITO/ZnO/CsPbBr3/TFB/MoO3/Ag 0.28 0.19 2335 2.8 523 19 [47] nano particle ITO/ZnO/CsPbI3/TFB/MoO3/Ag -5.7 206 -698 31 [47] nano particle ITO/ZnO/CsPbI3-nBrn/TFB/MoO3/Ag -1.4 1559 -619 29 [47] nano particle ITO/ZnO/CsPbBrnCln/TFB/MoO3/Ag -0.0074 8.7 -480 17 [47] Low dimension thin film ITO/TIO2/PEA2MAn-1PbnI3n+1/F8/MoO3/Au -8.8 80* 3.8 [16] thin film ITO/PEDOT:PSS/poly-TPD/BA2MA2Pb3I10/TPBi/LiF/Al 0.1 2.29 214 2.7 700 52 [191] thin film ITO/PEDOT:PSS/poly-TPD/BA2MA4Pb5Br16/TPBi/LiF/Al 3.48 1.01 2246 3.3 523 24 …”
Section: Light Harvester Light Emittermentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] A power conversion efficiency (PCE) of 22.1% has been certified on single-junction perovskite solar cells (PSCs), almost comparable to that of state-of-the-art crystalline silicon solar cells. [10] Besides the pursuit of an even higher PCE by enhancing perovskite film quality, [11][12][13][14][15] optimizing the device another key factor. [24] For example, the most widely investigated methylammonium (CH 3 NH 3 + or MA) lead iodide (MAPbI 3 ) is reported to undergo a phase transition at 54-57 °C [30,31] and degrade at temperature over 85 °C, [32] suggesting its poor thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of charge recombination in bulk film requires high quality perovskite film with full surface coverage [26][27][28], large crystal size [15,29,30] and low defect density [31][32][33]. The post-treatment using a strong Lewis base is a very effective method to improve the quality of lead halide perovskite films [34][35][36][37][38][39][40][41][42]. In 2014, Zhao et al [34] first found a room-temperature phase transformation of CH 3 NH 3 PbI 3 induced by ammonia.…”
Section: Introductionmentioning
confidence: 99%